Tolerance of gynecological cancer radiation therapy by women during and post menopause - Szczepanik, Krzysztof; Telka, Ewa; Jochymek, Bożena; Miśta, Wioletta; Kleszyk, Łukasz; Urbańczyk, Hubert (Menopause Review/Przegląd Menopauzalny, 2013)
Quality of life of patients with genital cancer, especially ovarian and endometrial cancer is reduced. In these patients, physical symptoms of the disease affect the reception of the sickness, and in general terms the quality of life. All therapeutic measures that reduce the severity of physical symptoms significantly improve the patient’s quality of life. You can also see the relationship between age and quality of life of patients with ovarian cancer. Lower quality of life of patients at the menopausal age relates to physical symptoms, and this area requires special care. A higher intensity of anxiety is also observed and thus, this group requires more attention and support in psychological, emotional and social terms. Also proper information provided by medical personnel, including midwives and nurses involved in the healing process, is of considerable importance. Persons exhibiting a higher degree of resourcefulness and understanding more easily find themselves in difficult situations, assess their psychosocial functioning and overall quality of their life better. Therefore, the ill that are fully informed and well-oriented in their disease and treatment used assess the quality of life much better. Currently, assessment of quality of life becomes an important element enabling a comprehensive assessment of the patient’s general state. In the case of patients with ovarian cancer there is a tendency that the quality of life is one of the essential elements of the efficacy, and impact on its value is a factor affecting its planning.